2001
DOI: 10.1001/archsurg.136.12.1396
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Ulcerative Colitis in Elderly Persons

Abstract: Medical therapy has changed the indications for surgery over the last 4 decades. Advances in perioperative care have significantly improved the outcome. Design: The medical records of all patients 65 years and older who underwent surgery for ulcerative colitis during a 40-year period were analyzed retrospectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Postoperative complications after surgery decreased from the years 1960–1984 to 1994–1999 and elderly age was not a predictor of adverse outcome. 69 There was no significant difference in morbidity or 30-day mortality between TPCI versus IPAA procedures. 70 The incidence of postoperative cardiac and pulmonary complications was higher in the elderly than in younger patients.…”
Section: Ibd Treatment In the Elderlymentioning
confidence: 81%
“…Postoperative complications after surgery decreased from the years 1960–1984 to 1994–1999 and elderly age was not a predictor of adverse outcome. 69 There was no significant difference in morbidity or 30-day mortality between TPCI versus IPAA procedures. 70 The incidence of postoperative cardiac and pulmonary complications was higher in the elderly than in younger patients.…”
Section: Ibd Treatment In the Elderlymentioning
confidence: 81%
“…Although older patients were thought to have higher rates of complications, while the mortality rates of patients requiring urgent surgery have been reported at as high as 50 % [1012], the number of elderly patients in those studies was small. Moreover, Almogy et al [13] reported emergency surgery, a low level of albumin, and male sex as predictors of an adverse outcome in their elderly UC population. Fewer complications and a lower death rate should be expected in elderly UC patients undergoing elective procedures.…”
Section: Discussionmentioning
confidence: 99%
“…These clinical considerations seem to be partially confirmed by the experience of Almogy et al [3]: in their series of elderly patients, in fact, they showed that TM is still associated with a high mortality rate (37.5%) which has not improved over time.…”
Section: Discussionmentioning
confidence: 72%
“…The lifetime risk of TM in patients with IBD has gradually decreased probably because of earlier diagnosis and more aggressive management of severe colitis [2, 3]. On the other hand, TM as a complication of infectious colitis is expected to increase [4] in proportion to the rapidly rising prevalence of pseudomembranous (due to broad-spectrum antibiotics) and CMV (due to HIV infection or immunosuppression) colitis.…”
Section: Introductionmentioning
confidence: 99%